1998
DOI: 10.1002/(sici)1099-1395(199802)11:2<115::aid-poc985>3.3.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical studies on the gas‐phase nucleophilic substitution reactions of benzyl chlorides with phenoxides and thiophenoxides

Abstract: Gas-phase nucleophilic substitution reactions of Y-benzyl chlorides with X-phenoxide and Xthiophenoxide nucleophiles were investigated theoretically using the PM3 semi-empirical MO method. The LefflerGrunwald rate-equilibrium and Brønsted correlations predict that the degree of bond formation in the transition state (TS) is approximately 45 and 40% on the reaction coordinate for the phenoxides and thiophenoxides, respectively. For a weaker nucleophile, a later TS is obtained with an increased bond making and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…Hence, analysis of the main factors responsible for the ratio between the enthalpy and entropy contribution to the energy barrier for the reaction is of great importance. In this regard, studies on substituent effects in BNRs have been the subject of intense interest . In most cases, substituent effects are quantified by the use of the Hammett or the Hammett‐like substituent constants for aromatic system …”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…Hence, analysis of the main factors responsible for the ratio between the enthalpy and entropy contribution to the energy barrier for the reaction is of great importance. In this regard, studies on substituent effects in BNRs have been the subject of intense interest . In most cases, substituent effects are quantified by the use of the Hammett or the Hammett‐like substituent constants for aromatic system …”
Section: Introductionsupporting
confidence: 71%
“…These include S N 2, acyl‐transfer, S N Ar, S N V, and Ad N reactions, etc . Various experimental kinetic and theoretical studies have therefore been devoted to obtain a better understanding of the mechanisms of these processes . Among traditional experimental methods, kinetic isotope effects and linear free energy relationship have most frequently been used to study mechanisms of BNRs, in particular the nature of transition states (TSs) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results from experimental kinetic and theoretical research on S N 2 reactions in the gas phase5–16 and in the solution17–31 have shown that a full understanding of the chemistry of such processes requires a detailed knowledge of the structural factors with respect to reactivity. Therefore, the effects of structural variations in the substrate, leaving group and nucleophile have received considerable attention 5–31. In this regard, linear free energy relationships (LFER) have been the most useful tool for studying S N 2 reactions in solution 1–4.…”
Section: Introductionmentioning
confidence: 99%